Gamification to develop coding skills - Martins, Ciro (2018)
Digital technologies are increasingly assuming a crucial role in daily routines and in our professional lives, and, thereof, they are more and more relevant to provide solid answers to emerging societal challenges. Nonetheless, in initial programming curricular units, it is not always easy to manage the students' different knowledge level, especially due to their diverse learning backgrounds. In this scenario, a teaching/learning strategy was designed to minimize the students’ heterogeneity (as well as the constraints that spur from it) and try to guarantee learning equity among them. Thus, the strategy was based on a flipped classroom approach, which implies the students’ autonomous work prior to face-to-face (in-class) work. For that purpose, two platforms were chosen with different purposes: i) Code Avengers was selected to create controlled, practical learning and teaching experiences in a gamified environment, and ii) Mooshak for the teacher for automatic assessment, to monitor and give feedback to students in online environment. The global perception as to the strategy implementation is that it has great potential, i.e. it had a positive impact on the students’ interest in developing coding skills, in particular due to its gamification facet and the instant feedback provided to students.